The dynamics of spiritual formation - Lawrenz, Mel (Grand Rapids,Mich. Baker Books, 2000)
Pastors and church leaders can use the normal activities of church life to touch the innermost lives of their flock, fostering spiritual growth and building up the body of Christ.
Keywords: Spiritual formation